Utilizing Cold Plasma in Preparing Silver Nanoparticle from Origanum Vulgare - Mazhir, Sabah N.; Ali, Iman A Mohammed; Al-Ahmed, Hazim I. (Iraqi Journal of Science, 2019)
In this research, we obtained nanoparticles (NPs) using a type of microwave (cold plasma) and water extract from Origanum vulgare with the addition of silver nitrate (AgNO3) solution. Silver nanoparticles are characterized by high production techniques. Experimental factors such as morphology, structure, optical properties and active compounds of the nanoparticle extract were studied through specific tests such as morphology, UV spectroscopy, FE-SEM, FT-IR, and Atomic Force Microscopy (AFM). Plants were used in manufacturing the nanoparticles, as plants are well known for their accessibility and applicability in different pathological areas. The current research provides information on the Green Union System of Nanoparticles. It is concluded that, under the influence of cold plasma, the nanoparticles increased the nanoscale size of the molecules and thus increased the aggregation and the transformation of the pink color of the nanocrystal line to brown due to increased absorption.